Optical Modelling and Analysis of a Non-Imaging Stationary Compound Parabolic Concentrator using Ray Tracing Technique - LI, CHUN PING (2018)
A modified CPC solar collector is proposed to analyse its optical performance. CPC collector is chosen from various types of solar collectors for the study due to its non-imaging (non-tracking) ability and focusing type. The CPC in this project is designed to have an absorber attached with fins and is enclosed in an evacuated tube to reduce the gap losses. The design will be examined and critical comparison with different concentration ratio will be carried out. Experimental work is not suitable to measure and visualize the absorbed solar radiation by the collector, therefore ray tracing technique is needed to obtain the optical efficiency and the 2D image of the ray tracing behaviour. MATLAB is used for the numerical analysis of optical efficiency and the calculated highest optical efficiency for a full height CPC is about 61.4 %, the drop is not significant for optical efficiency, highest incident energy on aperture is 636 W and highest energy absorbed is 386.7 W. The highest optical efficiency obtained by ray tracing technique is 76.7 %, the average drop in optical efficiency for different truncation ratio is about 1.09 % to 4.3 %, highest incident energy on aperture is 589 W and highest rate of energy absorbed is 417 W. Truncation ratio is a crucial factor to achieve the optimum design of CPC while maintaining the optical efficiency, a truncated CPC has a longer effective operating period than a non-truncated CPC, the 70% truncated CPC in this work can achieve 5 hours more effective period than the full height CPC with reduction in the optical efficiency due to less concentration ratio. For numerical analysis, the rate of energy absorbed reduced about 17 W to 33 W which is drop in 4 % to 9.5 % for increasing truncation ratio, and for ray tracing result, the rate of energy absorbed dropped about 28 W to 54 W or 7.7 to 12.9 %.